Tyrosine Phosphorylation Profiling Revealed the Signaling Network Characteristics of CAMKK2 in Gastric Adenocarcinoma - Najar, Mohd. Altaf; Arefian, Mohammad; Sidransky, David; Gowda, Harsha; Prasad, T. S. Keshava; Modi, Prashant Kumar; Chatterjee, Aditi (Frontiers in Genetics, 2022)
Calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) is a serine/threonine protein kinase which functions via calcium triggered signaling cascade with CAMK1, CAMK4, and AMPKα as immediate downstream substrates. CAMKK2 is reported to be overexpressed in gastric cancer however, its signaling mechanism is poorly understood. We carried out label-free quantitative tyrosine phospho proteomics to investigate tyrosine-mediated molecular signaling associated with CAMKK2 in gastric cancer cells. Using a high-resolution Orbitrap Fusion Tribrid Fourier-transform mass spectrometer, we identified 350 phosphotyrosine sites mapping to 157 proteins. We observed significant alterations in 81 phosphopeptides corresponding to 63 proteins upon inhibition of CAMKK2 among which 16 peptides were hyperphosphorylated correspond to 13 proteins and 65 hypophosphorylated correspond to 51 proteins. We report here that inhibition of CAMKK2 leads to changes in the phosphorylation of several tyrosine kinases including PKP2, PTK2, EPHA1, EPHA2, PRKCD, MAPK12, amongst others. Pathway analysis revealed that proteins differentially phosphorylated in response to CAMKK2 inhibition involved in focal adhesions, actin cytoskeleton, axon guidance, and signaling by VEGF. Western blot analysis upon inhibition and/or silencing of CAMKK2 revealed a decrease in phosphorylation of PTK2 at Y925, c-JUN at S73, and STAT3 at Y705, which was in concordance with the mass-spectrometry data. The study indicates that inhibition of CAMKK2 has an anti-oncogenic effect in gastric cells regulating phosphorylation of STAT3 through PTK2/c-JUN in gastric cancer.